2021
DOI: 10.1370/afm.2684
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features for the Diagnosis of Pediatric Urinary Tract Infections: Systematic Review and Meta-Analysis

Abstract: PURPOSE Accurate diagnosis of urinary tract infection in children is essential because children left untreated can experience permanent renal injury. We aimed to assess the diagnostic value of clinical features of pediatric urinary tract infection. METHODSWe performed a systematic review and meta-analysis of diagnostic test accuracy studies in ambulatory care. We searched the PubMed, Embase, Web of Science, Cumulative Index to Nursing and Allied Health Literature, Cochrane Central Register of Controlled Trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
0
9
0
5
Order By: Relevance
“…The medical IoTs support multiple access operations such as mobile terminal applications, which can realize urinary real-time nursing status monitoring and intelligent management. The urinary real-time nursing model uses cloud computing technology to build a centralized management model of medical nursing, which has great advantages compared with the traditional decentralized and independent model [ 17 ]. The establishment of patient nursing files on the basis of the medical IoTs is to record all the health information of each patient.…”
Section: Urinary Real-time Nursing Model Optimization For Medical Iotsmentioning
confidence: 99%
“…The medical IoTs support multiple access operations such as mobile terminal applications, which can realize urinary real-time nursing status monitoring and intelligent management. The urinary real-time nursing model uses cloud computing technology to build a centralized management model of medical nursing, which has great advantages compared with the traditional decentralized and independent model [ 17 ]. The establishment of patient nursing files on the basis of the medical IoTs is to record all the health information of each patient.…”
Section: Urinary Real-time Nursing Model Optimization For Medical Iotsmentioning
confidence: 99%
“…Diagnosis is challenging, as only a minority of children with UTI present with typical UTI symptoms. In a previous study, we found that changes in urine appearance, such as cloudy urine, malodorous urine and haematuria, are alarming signs for UTI, while only few features (e.g., circumcision, stridor) lower the probability of UTI considerably 5 …”
Section: Introductionmentioning
confidence: 89%
“…In a previous study, we found that changes in urine appearance, such as cloudy urine, malodorous urine and haematuria, are alarming signs for UTI, while only few features (e.g., circumcision, stridor) lower the probability of UTI considerably. 5 Because the clinical presentation is often unclear, primary care physicians need appropriate collection methods for urine testing…”
mentioning
confidence: 99%
“…Only a few features, such as circumcision in boys, nappy rash, or the presence of stridor decrease the probability of UTI. 6 The absence of signs and symptoms of UTI in children makes it difficult to rule out UTI at an early stage.…”
Section: Introductionmentioning
confidence: 99%